SpongeBob SquarePants. The complete second season [videorecording (DVD)] - Kenny, Tom; Bumpass, Rodger; Fagerbakke, Bill, 1957- (Paramount, 2004)
The adventures of nautical sea sponge SpongeBob Squarepants and his freinds in the underwater town of Bikini Bottom.